Building Awareness of the Safe and Responsible Use of Artificial Intelligence (AI) in the Higher Education Environment of Manado State University - Eka Nurindah Sari; Panji Tanashur; Rodearta Purba; Dimas Pujianto (STAI Nurul Islam Mojokerto, 2026)
The presence of Artificial Intelligence (AI) offers various benefits in supporting the learning process and various other aspects of daily life. However, along with this convenience, there are also challenges and risks in its use, such as misuse of technology, violations of academic integrity, the dissemination of inaccurate information, and risks to personal data security. Therefore, educational efforts are needed to raise awareness among the academic community regarding the safe and responsible use of AI. This community service activity aims to increase the understanding of lecturers and students regarding the ethical, safe, and responsible use of AI in the academic environment. The activity was held on November 22, 2025, at Manado State University, involving 59 participants consisting of lecturers and students. The methods used were educational seminars, interactive discussions, and evaluation through pre- and post-tests. The results of the activity showed an increase in participant understanding, indicated by an increase in the average score from 55.53 (moderate category) in the pre-test to 62.10 (High Category) in the post-test. These findings indicate that the educational activities implemented are effective in increasing AI literacy and building awareness of the safe and responsible use of AI in the higher education environment. Therefore, similar programs need to be implemented on an ongoing basis to support the creation of a digital culture that is safe, ethical, and adaptive to technological developments.